Fourth-Order Delay Differential Equations: New Monotonic Properties of Solutions (Contemporary Mathematics, 2025)
New oscillation criteria for the fourth-order delay differential equation are presented. An essential feature of our results is that oscillation of the studied equation is ensured via some conditions. Furthermore, new criteria are provided to delay differential equations by using the Riccati transform technique, the integrated averaging approach, and the comparison method with second order. Our results essentially improve, extend, and simplify some known ones reported in the literature. The results are illustrated with examples.
Keywords: delay; oscillation; fourth-order DEs